Bridging Knowledge and Practice: The Role of Knowledge Sharing and Transfer of Training in Enhancing SPG Performance - Suriadi; Jasiyah, Rabiyatul; Bahari, Samsul; Murini; Sultraeni, Wiwin; Hasddin; Mirad (Jurnal Aplikasi Manajemen, 2025)
In today’s highly competitive fast-moving consumer goods (FMCG) industry, sales promotion performance continues to face serious challenges due to the persistent imbalance between knowledge acquisition and its actual application in daily work practices. This issue is particularly evident among Sales Promotion Girls (SPG), whose performance directly affects customer engagement and company sales outcomes. This study aims to investigate how knowledge sharing and the transfer of training contribute to enhancing SPG performance at PT Unilever in Kendari City. Using a descriptive qualitative design, the study involved 25 key informants selected purposively from a population of 32 SPGs. Data were gathered through in-depth interviews, direct observation, and document analysis. The findings reveal that knowledge sharing significantly enhances performance through two dimensions: knowledge collecting (facilitated through formal training sessions, which increased conceptual understanding of product mastery and personal selling) and knowledge donating (through voluntary peer exchanges that strengthened practical competence). However, its effectiveness is often constrained by uneven knowledge distribution and limited institutional recognition. Successful training transfer is driven by field-based practice opportunities, cohesive teamwork, and motivation provided through reward systems. This study provides a novel perspective by highlighting how the integration of formal and informal knowledge flows can reinforce sustainable SPG performance and inform more adaptive human resource development strategies in dynamic sales environments.